Armed Conflict and Child Weight in DR Congo - Kien Le (Advances in Public Health)
This paper investigates the extent to which armed conflict influences the weight of young children in the Democratic Republic of the Congo. Exploiting the variation across districts in exposure to armed conflict and the within-district variation in the timing of whether the child was exposed to armed conflict due to birth timing within a difference-in-differences framework, we detect adverse impacts of conflict exposure to child weight. Specifically, experiencing armed conflict makes children weigh less for their age and weigh less for their height by 0.20 and 0.24 standard deviations, respectively. Armed conflict also increases the probability of children being underweight and wasted by 4.7 and 2.7 percentage points, respectively. Our heterogeneity analyses reveal that children of disadvantaged backgrounds, i.e., those born to low-educated mothers, poor mothers, and rural mothers, tend to be disproportionately affected. Our study calls for effective measures to mitigate the detrimental repercussions of armed conflict.